BANNERS OF THE CAUCASIAN WAR IN THE COLLECTION OF THE CAUCASUS MILITARY AND HISTORICAL MUSEUM: STORY AND FATE OF THE COLLECTION - Maksimcik, A N (History, Archeology and Ethnography of the Caucasus, 2015)
The article covers the history of the Caucasian war banner collectionof the North Caucasian mountaineers, which has been stored in the Caucasian Military and Historical Museum. The fate of these banners is directly connected with the history of the museum. The result of the work is correction of the existing information on banners stored in Makhachkala, Maikop and Tbilisi (history of the exhibits, time of their admission to the museum, description, the size of the flag and flagpole, currentstoring position, and the sources that provided information for the table of banners as well). To date the fate of 12 banners from the collection of the Caucasian Military and Historical Museum remains unknown. In addition, there is a complex of inoperative archival documents (archive of Trophy Committee), which could significantly complement the available information.
Keywords: Caucasian Military and Historical Museum; the Caucasian war; museum collection; banner